Renormalized Phonon Microstructures at High Temperatures from First-Principles Calculations: Methodologies and Applications in Studying Strong Anharmonic Vibrations of Solids - Tian Lan; Zhaoyan Zhu (Advances in Condensed Matter Physics)
While the vibrational thermodynamics of materials with small anharmonicity at low temperatures has been understood well based on the harmonic phonons approximation, at high temperatures, this understanding must accommodate how phonons interact with other phonons or with other excitations. To date the anharmonic lattice dynamics is poorly understood despite its great importance, and most studies still rely on the quasiharmonic approximations. We shall see that the phonon-phonon interactions give rise to interesting coupling problems and essentially modify the equilibrium and nonequilibrium properties of materials, for example, thermal expansion, thermodynamic stability, heat capacity, optical properties, thermal transport, and other nonlinear properties of materials. The review aims to introduce some recent developements of computational methodologies that are able to efficiently model the strong phonon anharmonicity based on quantum perturbation theory of many-body interactions and first-principles molecular dynamics simulations. The effective potential energy surface of renormalized phonons and structures of the phonon-phonon interaction channels can be derived from these interdependent methods, which provide both macroscopic and microscopic perspectives in analyzing the strong anharmonic phenomena while the traditional harmonic models fail dramatically. These models have been successfully performed in the studies on the temperature-dependent broadenings of Raman and neutron scattering spectra, high temperature phase stability, and negative thermal expansion of rutile and cuprite structures, for example.